THE ROLE OF KOREAN LANGUAGE IN MODERN GLOBAL CULTURE (International journal of artificial intelligence, 2025)
This article explores the growing significance of the Korean language in contemporary global culture. It examines how the rise of Korean popular culture, including K-pop, K-dramas, and Korean cinema, has propelled the language onto the world stage, fostering cross-cultural communication and influencing language learning trends worldwide. The paper also discusses the socio-economic and technological factors contributing to the Korean language’s international presence and considers its future role in global intercultural exchange.